PENGEMBANGAN MEDIA KARTU KUARTET UNTUK MEMFASILITASI PEMBELAJARAN PKN PADA KELAS V SDN 182 PEKANBARU - Berliana Effendi; Munjiatun Gacorr; M. Jaya Adi putra (STKIP Subang, 2026)
This study aims to develop quartet card learning media to facilitate Civic Education learning for fifth grade students at SDN 182 Pekanbaru. The background of this study stems from the minimal use of media and the dominance of lecture methods, which result in students being less active and learning becoming less interesting. The research used the Research & Development method with a 4D model that included the define, design, develop, and disseminate stages. In the define stage, an analysis of the curriculum, student characteristics, material, and learning needs was conducted. The design stage produced a quartet card design based on cultural diversity from 38 provinces. In the develop stage, validation was carried out by media experts, material experts, and language experts with an average feasibility of 89% (highly valid), as well as practicality tests with students and teachers, which each scored 86-91% (highly practical). Small group and limited group trials showed that this media was interesting, easy to use, and able to increase student engagement. In the dissemination stage, the product was submitted to schools as a ready-to-use learning medium. The results of the study indicate that the quartet cards are feasible and practical for use in civic education and have the potential to increase student motivation and understanding.